FRI0019 URINARY TRANSCRIPTS AS BIOMARKERS OF LUPUS NEPHRITIS. (June 2019) - Rosenwasser, Natalie; Hong, Seunghee; Walters, Lynnette; Nguyen, Phuong; Wang, Cindy; Baisch, Jeanine; Oxley, Peter; Ohouo, Marina; Caielli, Simone; Smitherman, Cynthia; Wang, Yuanyuan; Wright, Tracey; et al.
Abstract : Background: Children with systemic lupus erythematosus (cSLE) with kidney involvement face considerable morbidity and mortality. Commonly used methods for assessing kidney involvement in cSLE, such as renal function tests, are non-specific and provide a limited picture of disease activity. Kidney biopsy, the mainstay to assess disease class and chronicity as well as response to treatment, is an invasive procedure. The field of transcriptomics has identified markers that have helped our understanding of cSLE pathogenesis. Objectives: Transcriptional profiling of urinary cells has the potential to provide us with non-invasive biomarkers and has not been studied thus far. Our aim is to evaluate intracellular urinary transcripts in cSLE. Methods: Using the Human Inflammation v2 panel on the nanoString nCounter platform, expression of 255 genes was profiled from 82 urinary pellets (all from 43 cSLE with differing classes of lupus nephritis). Results: Healthy control samples yielded low quantities of RNA and were excluded from further analysis. The patient's raw transcript counts were normalized and the use of unsupervised learning analysis revealed robustness among classes with higher disease activity (higher SLE Disease Activity Index (SLEDAI) scoring). Statistical analysis (ANOVA) showed that Classes III or IV + V (mixed nephritis; highest average SLEDAI) display robust interferon and inflammasome-related signatures in comparison to other classes. Interestingly, samples from cSLE with no known nephritis also displayed an interferon signature, although less intense than the mixed class. Some transcripts such as C3 (complement 3) were uniquely dysregulated in the mesangial class. Therapeutically targetable pathways were identified in a number of patients (specifically in the mixed class). Conclusion: These studies are currently being extended in order to confirm the value of urinary transcriptional profiling as a source of biomarkers and to identify potential therapeutic targets in cSLE. References: [1] Pascual, et al., "Understanding Human Autoimmunity and Autoinflammation Through Transcriptomics, " Annu Rev Immunol, 2017 Apr 26;35:337-370. doi: 10.1146/annurev-immunol-051116-052225 [2] Bennett L, Palucka AK, Arce E, et al. Interferon and Granulopoiesis Signatures in Systemic Lupus Erythematosus Blood. The Journal of Experimental Medicine. 2003;197(6):711-723. doi:10.1084/jem.20021553. [3] Banchereau R, Hong S, Cantarel B, Baldwin N, Baisch J, et al. 2016. Personalized immunomonitoring uncovers molecular networks that stratify lupus patients. Cell 165:551–65 [4] Chiche L, Jourde-Chiche N, Whalen E, Presnell S, Gersuk V, et al. 2014. Modular transcriptional repertoire analyses of adults with systemic lupus erythematosus reveal distinct type I and type II interferon signatures. Arthritis Rheumatol. 66:1583–95 [5] Brunner H.I., Bennett M.R., Gulati G., Abulaban K., Klein-Gitelman M.S., Ardoin S.P., Tucker L.B., Devarajan P. Urine biomarkers to predict response to lupus nephritis therapy in children and young adults (2017) Journal of Rheumatology, 44 (8), pp. 1239-1248. Acknowledgement: Childhood Arthritis and Rheumatology Research Alliance Disclosure of Interests: None declared